Burnout of the physiotherapists and encountered stress factors related to coronavirus epidemic in Turkey - YILDIZ ÖZER, AYSEL (My University, 2023)
Purpose: The study aims to determine risk factors related to stress due to pandemic, the burnout levels of the physiotherapist, the relationship between these parameters. Methods: One hundred two physiotherapists, whose sociodemographic information was obtained, were divided into two groups according to disease exposure (CoV and non-CoV group). Pandemic-Associated Stress Factors of the participants were analyzed and Maslach Burnout Inventory (MBI) was used to measure burnout. The independent sample t test was used to detect the difference between the groups. Pearson's correlation analysis was used to find relations in parameters. Results: 96% of respondents were concerned about getting infected and 98% concerned about infecting their families. Most of the participants were physically and mentally tired (74.5%, 58.8%). The CoV group consisted of 45 (44.11%) physiotherapists who had a history of COVID-19, had patient contact, or worked with coronavirus patients. There was no significant difference in MBI subparameters between the two groups (p<0.05). Physiotherapists with high exposure to COVID-19 were found to have a 3.2 times higher level of stress about feeling compelled to go to work than those with low exposure to it (p=0.02). Conclusion: Anxiety about being sick and contagious can trigger psychological symptoms such as mental fatigue and sleep disturbance. Although the workload of the participants in our study did not increase, most of them stated that they felt physically exhausted. During the pandemic period, psychological diseases, and burnout in healthcare workers increased tremendously. Keywords: Coronavirus, Physiotherapist, Burnout.

Amaç: Bu çalışma pandemi kaynaklı strese bağlı risk faktörlerini, fizyoterapistin tükenmişlik düzeylerini, bu parametreler arasındaki ilişkiyi belirlemeyi amaçlamaktadır. Yöntem: Sosyodemografik bilgileri alınan 102 fizyoterapist hastalık maruziyetine göre (CoV ve CoV olmayan grup) iki gruba ayrıldı. Katılımcıların Pandemi İlişkili Stres Faktörleri analiz edildi ve tükenmişliği ölçmek için Maslach Tükenmişlik Envanteri (MTE) kullanıldı. Gruplar arasındaki farkı tespit etmek için bağımsız gruplarda t testi kullanıldı. Parametrelerdeki ilişkileri bulmak için Pearson korelasyon analizi kullanıldı. Bulgular: Ankete katılanların %96’sı enfekte olmaktan ve %98’i ailelerine bulaştırmaktan endişe duyuyordu. Katılımcıların çoğu fiziksel ve zihinsel olarak yorgundu (%74,5, %58,8). CoV grubu COVID-19 öyküsü olan, hasta teması olan veya koronavirüs hastalarıyla çalışan 45 (%44,11) fizyoterapistten oluşuyordu. MTE alt parametrelerinde iki grup arasında anlamlı fark yoktu (p<0,05). COVID-19'a yüksek maruziyeti olan fizyoterapistlerin, düşük maruziyeti olanlara göre işe gitmek zorunda hissetme konusunda 3,2 kat daha yüksek stres düzeyine sahip oldukları bulundu (p=0,02). Sonuç: Hasta olma ve bulaşıcı olma kaygısı, zihinsel yorgunluk ve uyku bozukluğu gibi psikolojik belirtileri tetikleyebilir. Çalışmamızda katılımcıların iş yükleri artmasa da çoğu fiziksel olarak bitkin hissettiklerini belirtmişlerdir. Pandemi döneminde rehabilitasyon hizmetlerinin önemli bir parçası olan fizyoterapistlerde psikolojik hastalıklar ve tükenmişliğin büyük oranda arttığı görülmektedir. Anahtar kelimeler: Koronavirüs, Fizyoterapist, Tükenmişlik.
Koronavirüs salgınında fizyoterapistlerin mesleki tükenmişlik düzeyi ve pandemiyle ilişkili karşılaşılan stres faktörleri
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Coronavirus; Physiotherapist; Burnout; Koronavirüs; Fizyoterapist; Tükenmişlik